TEXTUAL INTERPRETATION OF THE PROHIBITION OF MAKEUP: RECEPTION AND DISCOURSE ANALYSIS OF NUSSA GIRLS TALK - Rahmatullah Salam (UIN Raden Mas Said Surakarta, 2020)
This study aims to explain analytically the receptions of the Qur'an in the animated movie, episode Nussa: Girls Talk. A part of the Qur'anic verse from Surat Al-Ahzab: 33 presented in this episode shows that there are makeup rules for women that tend to be understood textually. Based on the categorization of interaction between religious followers and the holy book by Sam D. Gill and Teun A Van Dijk's critical discourse analysis as an analytical tool, the study found that the reception in the episode of Nussa: Girls Talk is both exegetical and informative. The interpretation (tafsir) presented in this episode is textual. The form of textual interpretation was chosen by the producers because of its concise and considered more relevant for children as the main targets/audiences. Besides, the socio-religious background of theproducers of Nussa: Girls Talk is known to have a close relationship with the hijrah movement; an Islamic movement that tends to be fundamentalist. As a results, textual understanding develops and tends to dominate in this animated movie.